Perspectives of Pharmacists, Doctors, and Nurses on Collaborative Management of Hypertension in Primary Health Centers - Nia Mariana Siregar; Hanni Prihhastuti Puspitasari; Wahyu Utami (Universitas Airlangga, 2023)
Background: Puskesmas is a primary healthcare facility that conducts chronic disease management, such as hypertension. The role of pharmacists in team collaboration includes that of managerial and clinical pharmacies. However, doctors and nurses still need to be fully aware of the role of pharmacists, particularly in clinical pharmacies. Objective: This study aimed to determine the perspectives of pharmacists, doctors, and nurses on the collaborative management of hypertension in health centres across the Central Lombok Regency. Methods: observational qualitative method with a maximum variation sampling technique was used. Data saturation was achieved after interviewing 27 participants between April and June 2023. Participants were pharmacists, doctors, and nurses responsible for managing hypertension in the selected primary healthcare centers. Results: Five main themes were identified. The first was a perspective on pharmacists' managerial and clinical pharmacy roles. Almost all participants agreed that pharmacists played more roles in ensuring the availability of hypertension drugs than clinical pharmacies. Four themes were derived from a conceptual framework related to team readiness to collaborate: cognitive, affective/relational, behavioral, and leadership aspects. In general, doctors and nurses need to be made aware of pharmacists' role in the area of clinical pharmacy; meanwhile, pharmacists need to improve their clinical pharmacy knowledge. Meanwhile, team collaboration has not run optimally because each team member works individually rather than as a team member. Conclusion: Pharmacists need to improve their clinical pharmacy role, be more involved in team collaborations, and be more engaged in team collaborations; efforts are required to prepare for team collaboration.